an educational research ISU SOSIAL-POLITIK DAN SOSIAL-BUDAYA DALAM PENDIDIKAN DASAR - Septiana, Eris; Mubariqah, Aulia Ismiyani; Emaliana; Lubis, Hasrita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary education has an important role in shaping students’ character, knowledge, and skills. However, the implementation of elementary education in Indonesia still faces various socio-political and socio-cultural issues that affect the quality and equity of education. This article aims to analyze socio-political and socio- cultural issues in elementary education through a literature study method. The research was conducted by reviewing various national and international journals relevant to the research topic. The results show that educational policies, curriculum changes, inequality of  educational access, local cultural influences, low literacy levels, technological developments, and socio-economic conditions influence the success of elementary education. In addition, the  successful implementation of elementary education is strongly influenced by government support, teacher competence, parental involvement, and the socio-cultural environment of society. Therefore, inclusive educational policies, equitable educational facilities, teacher competency improvement, and strengthening local cultural values are needed so that elementary education can develop optimally and in accordance with community needs.